Ranunculus huainingensis and R. lujiangensis (Ranunculaceae), described from Anhui in China, are both synonymous with R. ternatus, a polymorphic eastern Asian species - Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on literature survey and critical observations on herbarium specimens (including type material) and living plants in the wild, the variation in the presence or absence of filiform, tuberiferous stolons, shape and division degree of leaflets of basal leaves, shape, vein number and hairiness of sepals, presence or absence of nectary scale of petals, length of styles and shape of carpels are clarified for Ranunculus ternatus (Ranunculaceae), a polymorphic eastern Asian species very widely distributed in central and southeastern China. Ranunculus huainingensis and R. lujiangensis, both described from Anhui province in China, are revealed to lie within the variation range of R. ternatus. We therefore place both R. huainingensis and R. lujiangensis in synonymy with R. ternatus herein.